(untitled) (International Journal of Innovative Technologies in Economy, 2020)
The article reveals aspects of the formation of a complex mechanism of state regulation of territories economic potential development in Ukraine by improving the tools of its legal, organizational, informational, social and economic components. It is emphasized that the use of a separate functional mechanism significantly narrows the planned desired future outcome of transformations. It is proved that the combination into a single complex mechanism will ensure the highest efficiency of the public administration system, capable of self-reproduction in the long run. Practical recommendations for improving functional mechanisms as built-in elements of a complex mechanism of state regulation of territories economic potential development in Ukraine are given, which will improve the quality of executive bodies and local governments, will form the basis of modern business partnerships, strengthen economic opportunities at the local level in economic, social and environmental dimensions. It should reflect the strategic orientations of state building, be preventive in relation to future changes, take into account the turbulence of the external environment and give every citizen an awareness of stability and responsibility for the future of their own community.